Selection and experimental evaluation of shaking rods of canopy shaker to reduce tree damage for citrus mechanical harvesting - Pu, Yingjun; Toudeshki, Arash; Ehsani, Reza; Yang, Fuzeng; Abdulridha, Jaafar (International Journal of Agricultural and Biological Engineering, 2018)
Canopy shaking system is one of the research hotspots for large-scale mechanized fruits harvesting. Shaking rods considered as one of the essential components of canopy shaker are responsible for transferring mechanical energy from shaking mechanism to different regions of tree canopy. This transfer depends on the characteristics of the shaking rods that directly strike the tree canopy. In order to evaluate the effects of the shaking rods on tree damage level and fruit removal percentage, three kinds of shaking rods with different materials or shapes were selected. Based on the results of bending deformation tests, it was proven that the rigid shaking rod (R1) with the material of Polyvinyl Chloride (PVC) did more resistance against producing bending deformation in comparison with the other two types of shaking rods with the material of Polyamide Nylon 12 (PA). By contrast, the position close to the free end of the flexible shaking rod was easier to be deformed by less external force. In addition, dynamic analysis and vibration performance tests indicated that the rigid shaking rod could produce stronger vibration with higher shaking frequency of 4.8 Hz and maximum acceleration of 31.4 m/s2. Finally, the results of field trials indicated that the flexible bow-shaped shaking rod (R3) has a better widespread performance to achieve comparative higher fruit removal percentage up to 82.6% while producing lower tree damage rate of 5.36%. This study demonstrates that the materials or shapes of the shaking rod could significantly influence the fruit detachment rate and tree damage level. This study would provide an essential reference for the application of shaking rods for canopy shaker.Keywords: citrus harvester, shaking rod, canopy shaker, bending deformation, tree damage, fruit removalDOI: 10.25165/j.ijabe.20181102.4126Citation: Pu Y J, Toudeshki A, Ehsani R, Yang F Z, Abdulridha J. Selection and experimental evaluation of shaking rods of canopy shaker to reduce tree damage for citrus mechanical harvesting. Int J Agric & Biol Eng, 2018; 11(2): 48–54.